THE LEGACY OF âTASAWUF AKHLAQIâ SHEIKH SHOLEH DARAT AND SHEIKH IHSAN JAMPES - Bizawie, Zainul Milal (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2017)
One of the Nusantaras legacy is tasawuf akhlaqi (morals sufism). Since walisongoâs era, this sufism pervades and color the spread of Islam in Nusantara. From various works of the heritage of Nusantara of the hereditary breath tasawuf akhlaqi. The works of Sheikh Sholeh Darat and Sheikh Ihsan Jampes can explain how this Sufism dialogue with the local people to be easily executed. With the search of this tasawuf akhlaqi, will be the entrance to map the genealogy of thought, the historical foundation and espitemologis formula in recognizing the identity of a religious nation, especially related to morals. This becomes important, because during this nations identity increasingly away from the values that have been embedded in Nusantara. In this paper, it is asserted that Islamic tradition in Indonesia has become one of the founders and sustainers of the nations current identity. These traditions leave behind various socio-cultural heritages that need to be traced and found especially to the transmission of Islam into Nusantara. The socio-cultural heritage has become one of the foundations of massively constructed Indonesian identity, which later became the foundation of Indonesian Islam today, that is tolerant, moderate, peaceful and open attitude. The legacy of Nusantara Scholars, also affect the extent to which the relation and interaction of scholars form a network of knowledge and culture passed on to the next generation. There are two figures and works or manuscripts that are the focus of this paper: Sheikh Sholeh Darat Semarang and Sheikh Ihsan Jampes, which has brought understanding to tasawuf akhlaqi from al Ghazali in strengthening the identity of the Indonesian nation with a foundation of etiquette and politeness.